Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Grave marker of Amos J. Watkins (8/31/1896-12/6/1946); Albert Watkins 'oldest brother Chattanooga Memorial Park